International Arbitration in Germany - Wegen, Gerhard; Barth, Marcel; Wexler-Uhlich, Roman (Verlag C.H.BECK Recht - Wirtschaft - Steuern, 2022)
This new handbook deals with arbitration cases in Germany and cases governed by German law, both ad-hoc and institutional. It covers the following issues: Legal framework for international arbitration in Germany Considering arbitration for disputes in Germany (advantages of international arbitration; German institutional vs. ad-hoc arbitration; preparing for dispute in Germany) The arbitration agreement (formation, scope, effect, amendment, and termination of the arbitration agreement) The arbitral tribunal (jurisdiction; party autonomy; constitution of arbitral tribunal; contractual relationship between the arbitrators; rights of arbitrators; challenge of arbitrators; replacement of arbitrators) The arbitral procedure (the governing laws; place of arbitration and location of hearings; language of the arbitral proceedings; commencement of the arbitral proceedings; pleadings; oral hearing; default of a party; interim measures; state court assistance of arbitration; termination of arbitral proceedings) The arbitral award (applicable substantive law; the making of the award; content and form; delivery; types of awards; legal effect; publication; correction, and interpretation of award) Settlement (private settlement without award; award on agreed terms)